Nano-bio-sensing - Carrara, Sandro (Springer, 2011)
Nano-Bio-Sensing edited by: Sandro Carrara With Foreword by Giovanni De Micheli The application of engineering principles to problems in medicine has led to the emergence of biomedical circuits and systems as an exciting and rapidly growing area of research. Nanotechnology provides new structured materials with amazing properties, which can be applied to develop advanced instrumentation for biomedical diagnostics and personalized therapy, as well as bio-sensing in the environment. Biotechnology provides new bio-molecules with novel properties that can be applied to obtain new performance in sensing techniques. These advancements in Nano- and Bio- technologies will lead to new concepts and applications for nano-bio-sensing systems. This book offers an invaluable reference to the principles and practice of nano-bio-sensing. It brings together expertise of researchers from the fields of nano-electronics and bio-technology, providing multidisciplinary content from nano-structures fabrication to bio-sensing applications. It covers extensively the basic principles of interaction of living matter with detectors and transduction principles. It reviews surface science, as well as electrical and optical technologies for bio-sensing. Nano-scale effects, inducing quantum confinement, are specifically addressed along with their benefits, such as the amplification of sensing phenomena, yielding devices with higher sensitivity. Particular emphasis is given to low-power sensing techniques, as well as non-conventional means for powering the sensors, which may be very useful for implanted biosensors. Reviews all of the most advanced nano-bio-sensing techniques; Provides multidisciplinary reference to state-of-the-art applications of nano-bio-sensing; Includes a wide range of application areas, including patient diagnosis and personalized therapy, as well as bio-sensing in the environment; Includes a variety of real examples using nano-materials for bio-sensing purposes; Describes uses of nanotechnology and biotechnology for designing innovative biochips; Anticipates future developments in fault-tolerant and error-free biochips.